2017
DOI: 10.1177/2059436417728855
|View full text |Cite
|
Sign up to set email alerts
|

You are what you post in “circle of friends” of WeChat: Self-presentation and identity production from a personality perspective

Abstract: Social media services have become increasingly important in Chinese people's daily lives, and among them, WeChat is one of the most popular applications. There have been studies examining individuals' practices of self-presentation and identity production in various online platforms, and they have found the impact of anonymity on users' presentation and construction of self. However, little is known about whether users present their actual self or construct new identities different from those in their offline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Impression management and self-presentation are usually discussed together and used interchangeably (Kramer & Haferkamp, 2011). Scholars have also extensively studied self-presentation in social media contexts (Bullingham & Vasconcelos, 2013;Ellison et al, 2006;Hogan, 2010;Lin et al, 2017;Marwick & Boyd, 2010). An individual's online profile, including avatars, interests, affiliations, friends lists, and status updates, as well as digitized activities such as likes, dislikes, comments, and location tagging on social media platforms (Chua & Chang, 2016;Mendelson & Papacharissi, 2011;Silva & Frith, 2012) can all be conceptualized as "expressive equipment" (Goffman, 1959, p. 22) to present oneself, crafted in the form of texts, photos, audios, videos, and web links.…”
Section: Online Privacy and Self-presentationmentioning
confidence: 99%
“…Impression management and self-presentation are usually discussed together and used interchangeably (Kramer & Haferkamp, 2011). Scholars have also extensively studied self-presentation in social media contexts (Bullingham & Vasconcelos, 2013;Ellison et al, 2006;Hogan, 2010;Lin et al, 2017;Marwick & Boyd, 2010). An individual's online profile, including avatars, interests, affiliations, friends lists, and status updates, as well as digitized activities such as likes, dislikes, comments, and location tagging on social media platforms (Chua & Chang, 2016;Mendelson & Papacharissi, 2011;Silva & Frith, 2012) can all be conceptualized as "expressive equipment" (Goffman, 1959, p. 22) to present oneself, crafted in the form of texts, photos, audios, videos, and web links.…”
Section: Online Privacy and Self-presentationmentioning
confidence: 99%
“…Hua (29, female, PhD student, Shanghai) Similar to Hua, many respondents believe that readers can already get an idea about the person through his or her reposts about the famous. A previous study has shown that the content posted on 'circle of friends' can reflect the user's real personality traits (Lin et al 2017). The behaviour of reposting itself, as some respondents suggest, is a sign of recognition.…”
Section: Discussing Celebrities In Everyday Lifementioning
confidence: 97%
“…We chose WeChat profiles as stimuli since WeChat is one of the most popular social networking sites (SNSs) in China (Lin et al, 2017). Moreover, as noted earlier, the layout and content of WeChat profiles are more straightforward compared to other SNS profiles.…”
Section: Stimuli and Manipulationmentioning
confidence: 99%